Ultraviolet radiation, vitamin D and the development of obesity, metabolic syndrome and type-2 diabetes. Issue 3 (23rd December 2016) - Gorman, Shelley; Lucas, Robyn M.; Allen-Hall, Aidan; Fleury, Naomi; Feelisch, Martin
Abstract : Obesity prevalence is increasing around the world; however, the causes are not known. Here, we discuss moderate sun exposure as a potential modifier of obesity and metabolic dysfunction, with a focus on sun-induced mediators such as vitamin D and nitric oxide. Abstract : Obesity is increasing in prevalence in many countries around the world. Its causes have been traditionally ascribed to a model where energy intake exceeds energy consumption. Reduced energy output in the form of exercise is associated with less sun exposure as many of these activities occur outdoors. This review explores the potential for ultraviolet radiation (UVR), derived from sun exposure, to affect the development of obesity and two of its metabolic co-morbidities, type-2 diabetes and metabolic syndrome. We here discuss the potential benefits (or otherwise) of exposure to UVR based on evidence from pre-clinical, human epidemiological and clinical studies and explore and compare the potential role of UVR-induced mediators, including vitamin D and nitric oxide. Overall, emerging findings suggest a protective role for UVR and sun exposure in reducing the development of obesity and cardiometabolic dysfunction, but more epidemiological and clinical research is required that focuses on measuring the direct associations and effects of exposure to UVR in humans.